2022
DOI: 10.1155/2022/3056109
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Warming Needle Moxibustion and Drug Therapy for Treating Knee Osteoarthritis: A Systematic Review and Meta-analysis

Abstract: Objective. To compare the efficacy of warming needle moxibustion (WNM) with that of drug therapy for treating knee osteoarthritis (KOA), so as to provide evidence-based reference for the treatment of knee osteoarthritis. Methods. PubMed, Embase, Cochrane Library, VIP, WanFang, and CNKI were searched from inception to March 23, 2022. Literature selection was processed in strict accordance with inclusion and exclusion criteria. Cochrane Risk of Bias Assessment tool was applied for quality assessment of included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Warm needle acupuncture (WNA), a therapy of combining acupuncture with moxibustion, is to insert the moxa into the needle that is punctured, and the heat energy is transferred to the acupoints through the needle body. Compared with drug therapy and other TCM, WNA may be more effective in the treatment of KOA, 15 , 16 such as alleviating pain and stiffness, promoting functional recovery, and improving life quality. Sun et al 17 found that WNA combined with meloxicam and comprehensive nursing can improve pain, mobility, stability, the ability to walk, go up and down stairs, and can also reduce the levels of prostaglandin E2 (PEG2), substance P (SP), dopamine (DA), and 5-hydroxytryptamine (5-HT) in serum.…”
Section: Clinical Application Of Traditional Chinese Non-pharmacologi...mentioning
confidence: 99%
“…Warm needle acupuncture (WNA), a therapy of combining acupuncture with moxibustion, is to insert the moxa into the needle that is punctured, and the heat energy is transferred to the acupoints through the needle body. Compared with drug therapy and other TCM, WNA may be more effective in the treatment of KOA, 15 , 16 such as alleviating pain and stiffness, promoting functional recovery, and improving life quality. Sun et al 17 found that WNA combined with meloxicam and comprehensive nursing can improve pain, mobility, stability, the ability to walk, go up and down stairs, and can also reduce the levels of prostaglandin E2 (PEG2), substance P (SP), dopamine (DA), and 5-hydroxytryptamine (5-HT) in serum.…”
Section: Clinical Application Of Traditional Chinese Non-pharmacologi...mentioning
confidence: 99%
“…The clinical treatment effect of acupuncture therapy is better than that of conventional therapy such as oral administration. [ 12 ] Many scholars have conducted evidence-based medical research. Tian et al [ 13 ] published a systematic review in 2022 and believed that acupuncture has a beneficial effect in relieving pain and improving functional activities.…”
Section: Introductionmentioning
confidence: 99%
“…특히 적외선 조사기나 찜질팩과 같은 피부의 온도를 높이는 온열 자극 에 비해 온침은 호침을 통해 온열 자극이 전해지기 때문에 더 깊은 층의 조직까지 온열 자극을 전달할 수 있다 2) . 온침치료의 임상적 호전의 예로는 골관절염, 류마티스 관절염, 요추 추간판 탈출증, 경추성 두통과 같은 통증질환에 활용한다는 연구가 있으며 [3][4][5][6] , 뇌졸중 이후 일상 생활의 회복, 알츠하이머 환자 의 인지기능 및 일상 생활능력 향상시켰다는 치료 효과가 보고된 바 있다 7,8) . 그러나, 전통적인 온침치료는 애융(艾絨)을 태워서 열자극을 얻 는 방법이다.…”
unclassified